Psychological adjustment in the stepchild-stepparent relationship (2002)
Step relationships appear here to staay and the issue of stepparent and stepchildren are no longer as alien in Nigeria as it was some decades ago. Research interest in this phenomenon in Nigeria is an important addition to research interest in the area of psychological adjustment. The study set out to examine the coping behaviours that stepparents and step children often make use of in thier bid to adjust psychologically to the stress of step-relationship. It also examined the pattern of cordial relationship on six factors in step relationships arising from death and from divorce circumstances. Using 66 stepchildren and 48 stepparents and research instruments, the study showed that there is no significant difference in the mst often used coping behaviours of stepparents and stepchildren. Also the attempts to be cordial relationship between step parents and stepchildren whose step-relationship arose from death circumstances than between those which arose from divorce sircumstances. The use of coping behaviours and establishement of cordial relationships have implications for stepparent stepchildren relationship.